The Tenth Conference on Applied Linguistics and the Second English Language Teaching and Technology Conference in Collaboration 2017
DOI: 10.5220/0007173206830688
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Puppet in Teaching Speaking to Young Learners

Abstract: | repository.upi.edu | perpustakaan.upi.edu CHAPTER I INTRODUCTION This chapter presents an introduction of the research paper which describes the background of the research, research questions, aims of the study, and significances of the study. In addition, the organization of this research paper is also presented at the end of the chapter. 1.1 Background of The Study English has been taught in all levels of education in Indonesian primary schools with greater compulsion, and at a steadily lowering age (Gradd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many studies proposed some learning models or techniques while using puppets in ELT to improve students" language skills. Some studies found that puppets can be an effective medium and material to promote students" speaking competencies [9], [10], [11]. However, no study is investigating how using puppets, exclusively the Javanese puppets in PBL can promote students" four language skills.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies proposed some learning models or techniques while using puppets in ELT to improve students" language skills. Some studies found that puppets can be an effective medium and material to promote students" speaking competencies [9], [10], [11]. However, no study is investigating how using puppets, exclusively the Javanese puppets in PBL can promote students" four language skills.…”
Section: Introductionmentioning
confidence: 99%